Has the seasonal workers directive missed its target? Evidence from Italy during the pandemic. Issue 3 (September 2022) - Passalacqua, Virginia
Abstract: In 2014, the European Union adopted the Seasonal Workers Directive to achieve a twofold aim: meeting employers' demand for flexible and cheap labour and enhancing protection for third-country national (TCN) workers. Especially Article 23, the equal treatment provision, triggered a cautious optimism among scholars and trade unions, which looked at the Directive as a source of increased protection for seasonal workers. However, trade unions also pointed out the limited reach of the Directive, criticising its lack of commitment and ambition. Over the years, and especially during the Covid pandemic, it became clear that the Seasonal Workers Directive did not represent a game-changer for TCN seasonal workers, whose increased protections remained true only on paper. This contribution draws on the case of Italy during the pandemic to understand the reasons for the Directive's limited impact. The article critically examines the different political tensions underpinning the adoption of the Directive, to better understand why the Directive is not applied in practice and how it impacts the labour market and migrants' social conditions.